Duplicity of the indirect object in Spanish: sociolinguistic study - Alarcón Marcapura, Dany (2002)
Syntactic structures that present duplication of indirect object in the colloquial use of the Spanish language are analyzed. The use of duplicate forms in Spanish is a practice that is observed daily, especially at the level of orality. The double use of the indirect object is very productive in the Spanish language and occurs with emphatic purposes even in social strata considered cultured or literate. The function of unstressed pronouns as elements on which the duplicated forms we allude to are supported is also studied.